UNDERSTANDING WHAT IT WAS: URBANIZATIONAND WATER CRISIS IN THE CITY OF MUTARE IN MANICALAND PROVINCE- ZIMBABWE - Kanjanda, Offard; Chiparange, Getrude Vongai (European Scientific Journal, ESJ, 2014)
Once the pride of the eastern region,the city of Mutare has turned into an unbelievable state because of the water crisis. A survey was conducted in the high density suburbs of Dangamvura, Hobhouse and Chikanga 3 to establish the impact of water crisis to the residents of these areas. The quantitative paradigm was used in this study. In order to collect the data, the researchers triangulated some instruments such as direct observation, questionnaire and interview. From a population of 10 000 houses, 100 houses were selected using the stratified sampling, systematic and purposive techniques. Each house was represented by one person and the sample had 60 females and 40 males. The purposive sampling technique was used to collect data from the local authorities. Direct observation was conducted at some water collection points during daytime and at night. The collected data were presented in tables, pie -charts, graphs and descriptive. The research findings were that, child labour is on the increase in these areas because children carry large plastic containers of water and push them in wheelbarrows for long distances. Water crisis has caused some health hazards as people are forced to use the water very sparingly. Pedestrians compete with traffic for space on the narrow and rugged roads, causing danger to human life. Dust from traffic pollutes the uncovered water thereby increasing more unhealthy conditions to people. Poor planning and management system by the local authorities has created human suffering, especially children who need more time to study. The study recommended that the local authorities should drill boreholes at some strategic points for residents. Old pipes should be replaced as they no longer sustain the ever increasing population in the city. Water shortage should be for few hours and not for the whole day or days to avoid unhygienic practices in houses.